Odanacatib, a selective cathepsin K inhibitor to treat osteoporosis: safety, tolerability, pharmacokinetics and pharmacodynamics – results from single oral dose studies in healthy volunteers. (8th April 2013) - Stoch, S. Aubrey; Zajic, Stefan; Stone, Julie A.; Miller, Deborah L.; van, Lucas; Lasseter, Kenneth C.; Pramanik, Barnali; Cilissen, Caroline; Liu, Qi; Liu, Lida; Scott, Boyd B.; Panebianco, Deborah; et al.
<x xml:space="preserve">Abstract</x> Aims To evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of odanacatib (ODN), a cathepsin K inhibitor, in humans. Methods Two double‐blind, randomized, placebo‐controlled, single oral dose studies were performed with ODN (2–600 mg) in 44 healthy volunteers (36 men and eight postmenopausal women). Results Adverse experiences (AEs) with single doses of ODN were transient and mild to moderate, with the exception of one severe AE of gastroenteritis. Headache was the most frequent AE. After absorption of ODN (initial peak concentrations 4–6 h postdose), plasma concentrations exhibited a monophasic decline, with an apparent terminal half‐life of ∼40–80 h. The area under the curve0‐24 hours (AUC0–24 h), concentration at 24 hours (C24 h) and maximum concentration (Cmax, overal) increased in a less than dose‐proportional manner from 2 to 600 mg. Administration of ODN with a high‐fat meal led to ∼100% increases in AUC0–24 h, Cmax, day1, Cmax, overall and C24 h relative to the fasted state, while administration with a low‐fat meal led to a ∼30% increase in those parameters. Reduction of biomarkers of bone resorption, the C‐ and N‐telopeptides of cross‐links of type I collagen, (CTx and NTx, respectively), was noted at 24 h for doses ≥5 mg and at 168 h postdose for ≥10 mg. In postmenopausal women administered 50 mg ODN, reductions in serum CTx of −66% and urine NTx/creatinine (uNTx/Cr) of −51% relative to placebo were observed at 24 h. At 168 h, reductions in serum CTx (−70%) and uNTx/Cr (−78%) were observed relative to baseline. Pharmacokinetic/pharmacodynamic modeling characterized the ODN concentration/uNTx/Cr relation, with a modeled EC50 value of 43.8 nM and ∼80% maximal reduction. Conclusions Odanacatib was well tolerated and has a pharmacokinetic and pharmacodynamic profile suitable for once weekly dosing.